Characteristics of hydraulic fracture penetration behavior in tight oil with multi-layer reservoirs - Meng Cai; Wei Wang; Xianjun Wang; Liang Zhao; Hongtao Zhang (Energy Reports, 2023)
The tight oil reservoirs of Fuyang and Gaotaizi in the Daqing Oilfield exhibit characteristics such as thin layers and distributed barriers, which pose challenges for maintaining drilling accuracy within the desired geological sweet spot. Hydraulic fracturing has emerged as the optimal method to connect production wells with target layers effectively. Understanding the behavior of hydraulic fracture propagation in multiple thin layers with significant differences in mechanical properties is crucial for assessing the extent of effective drainage. In this study, a finite element numerical simulation model incorporating cohesive elements is employed to investigate and quantify the effects of stress differences and rock mechanical parameters on fracture penetration. The results indicate that the stress difference between the reservoir and barrier layers plays a key role in controlling hydraulic fracture penetration and height. Moreover, the flow rate and viscosity of the fracturing fluid have a noticeable impact on fracture progression. Hydraulic fractures tend to propagate along the interface of layers with low flow rate and fluid viscosity, thereby hampering the penetration performance in those layers. To achieve a comparable penetrated fracture length in low permeability reservoirs, it is necessary to increase the volume of fracturing fluid in high permeability reservoirs. Furthermore, the barriers layers, which possess relatively weaker mechanical properties, can constrain the width development of hydraulic fractures. This limitation may result in the risk of excessive liquid without sufficient proppant (commonly known as “over liquid but no sand”). Therefore, appropriate measures should be implemented to increase the net pressure and avoid encountering this complex situation.